The most ancient caviine rodent (Hystricognathi, Cavioidea) comes from the late Miocene of Northwest Argentina (South America) - Madozzo Jaén, María Carolina (2017)
The family Caviidae is one of the most diverse groups among South American hystricognath rodents and is represented by three main living lineages: Caviinae (cavies), Dolichotinae (maras) and Hydrochoerinae (capybaras). Caviinae includes the smaller forms of caviids represented by the extant Microcavia, Cavia and Galea. They are distributed in a wide range of environments throughout South America. In addition, three other genera from the late Miocene–Pliocene (Dolicavia, Palaeocavia and Neocavia) are recognised in high latitudes. In northwestern Argentina, the fossil forms of Caviinae have been poorly studied and for most of them there is no precise stratigraphic information. We describe and evaluate the phylogenetic affinities of the most ancient caviine from the Chiquimil Formation, Catamarca province, northwestern Argentina (9.14–7.14 ma). According to the morphological analysis of the mandibular and dental morphology and the results of the phylogenetic analysis, we assigned the new species tentatively to genus Palaeocavia. The phylogenetic position of the new species suggests an earlier origin for the lineage Palaeocavia + Cavia and for the entire clade Caviinae.